Ecology of Planktonic Atlantic Cod (Gadus morhua) (2017)
Atlantic cod larvae surviving the first weeks after hatching settle next years juvenile recruitment on Georges Bank (USA). It probably supports Hjort’s critical period hypothesis that effects of climate on marine biological productivity control early-life history processes and recruitment in fish populations. Climate also regulates local ultraviolet sea surface radiation, which may potentially kill microbes pathogenic to planktonic cod eggs. Survival capacities of cod larvae depend on maternal effects on egg qualities attained during oogenesis, influenced by variable food sources for female cod. Actual survival of first-feeding cod larvae requires proper abundance of preferred prey, copepod nauplii, produced by fertile females. Temporal and spatial mismatch between cod larvae and prey is normal, extensive and lethal, counteracted by opportunistic behavior that optimizes encounters. In spawning habitats of Northeast Arctic cod, the abundance of Calanus finmarchicus nauplii possibly results from coastal biological productivity in the previous year, which may explain time lags in positive correlations between vernal river discharge and NEA cod recruitment. Extensive meltwater storage for year-round hydroelectric production probably limits food web productivity, survival of NEA cod larvae and stock recruitment. Global climate change and stock management interact ecologically with other anthropogenic influences concerning sustainability of Atlantic cod population systems.